Usability assessment of the SESAME application in Myanmar: Specialized expert system for agro-meteorology early warning - Alliance of Bioversity International and CIAT; International Institute of Rural Reconstruction; Regional Integrated Multi-Hazard Early Warning System (DeRISK SE Asia, 2022)
This report presents the results based on the assessment carried out by the International Institute of Rural Reconstruction (IIRR) through DeRISK SE Asia project to define the potential entry points for intervention to improve the quality of users’ interaction with and the perception of the Specialized Expert System for Agro-Meteorology Early Warning (SESAME) system by an understanding of their needs, priorities, and preferences.